The neural basis of reversal learning: An updated perspective. (14th March 2017) - Izquierdo, A.; Brigman, J.L.; Radke, A.K.; Rudebeck, P.H.; Holmes, A.
Highlights: Reversal learning is a widely used test of cognitive flexibility across species. The idea that this learning primarily measures response inhibition has been revised. We describe how it is measured and present new definitions for its construct validity. We also present an update of the brain regions and neurotransmitters that support it. Abstract: Reversal learning paradigms are among the most widely used tests of cognitive flexibility and have been used as assays, across species, for altered cognitive processes in a host of neuropsychiatric conditions. Based on recent studies in humans, non-human primates, and rodents, the notion that reversal learning tasks primarily measure response inhibition, has been revised. In this review, we describe how cognitive flexibility is measured by reversal learning and discuss new definitions of the construct validity of the task that are serving as a heuristic to guide future research in this field. We also provide an update on the available evidence implicating certain cortical and subcortical brain regions in the mediation of reversal learning, and an overview of the principal neurotransmitter systems involved.